LIQUIDITY RISK ANALYSIS IN ISLAMIC AND CONVENTIONAL BANKS: A COMPARISON DURING THE COVID-19 PANDEMIC - Dzikrulloh, Chanif; Canggih, Clarashinta (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
The COVID-19 pandemic has had a major impact on the global economy including Indonesia, especially on the banking sector. This study uses a comparative quantitative research method. This study aims to compare risk in Islamic and conventional banks using the t-Test and Mann-Whitney U test. During the COVID-19 pandemic, the data shows differences in current ratio, quick ratio, and LDR/FDR between conventional and Islamic banks. Islamic banks have a higher current ratio and quick ratio than conventional banks, indicating a better ability to meet short-term obligations and maintain liquidity. In addition, Islamic banks have a lower FDR. The results of the study can help investors in making investment decisions, but it is recommended to also consider other indicators. The study only focuses on analyzing liquidity risk in both types of banks during the pandemic, suggesting future research to expand the variables and research time.